THIOPURINE METABOLITES IN THE MANAGEMENT OF PATIENTS WITH INFLAMMATORY BOWEL DISEASE: A SINGLE CENTRE EXPERIENCE OF 100 SAMPLES. (8th June 2013) - Hall, P S J; Ferguson, C B; Imrie, C; Lynch, M; Neely, A; Morrison, G
Abstract : Introduction: Thiopurine drugs are metabolised by a complex network of enzymes, each with individual genetic variability. Measurement of active metabolites, 6-thioguanine nucleotide (6-TGN) and 6-methylmercaptopurine nucleotide (6-MMPN), can have a role in optimising therapy for inflammatory bowel disease (IBD) patients.1 Aims/Background: To evaluate how testing thiopurine metabolite(TPM) levels affects the management of patients with IBD receiving azathioprine or 6-mercaptopurine. Method: A retrospective laboratory database search for TPM levels. The results were analysed in conjunction with outpatient letters and concurrent laboratory data. The primary outcome: how had measuring TPM levels affected patient management? Secondary objective: to combine demographic and test result data to provide information on the patterns of thiopurine drug use in this population. Results: One hundred samples from 78 patients. 45% of samples led directly to changes in patient management. 15% led to dose escalation whilst 9% required dose reduction. The results of 8% led to the use of biological therapy. Treatment was stopped due to potential toxicity in 3%. In 8% of samples, patients were found to be poorly compliant with thiopurine treatment. 3 patients were completely non-compliant. In a sub-group of patients with low Thiopurine S-methyltransferase (TPMT), 78% had high levels of TGN despite the use of low drug doses.Figure 1 Figure 2 Figure 3 Conclusion: Measuring TPMs is useful in the management of patients with IBD on thiopurines. They can reveal non-compliance and lead to dose alterations, treatment escalations and the prevention of drug toxicity. We would support the wider use of TPM testing in these patient groups.